2016
DOI: 10.1007/s11816-016-0388-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards better insect management strategy: restriction of insecticidal gene expression to biting sites in transgenic cotton

Abstract: Most of the commercialized Bt crops express cry genes under 35S promoter that induces strong gene expression in all plant parts. However, targeted foreign gene expression in plants is esteemed more important as public may be likely to accept 'less intrusive' expression of transgene. We developed plant expression constructs harboring cry1Ac gene under control of wound-inducible promoter (AoPR1) to confine Bt gene expression in insect wounding parts of the plants in comparison with cry1Ac gene under the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
(59 reference statements)
0
7
1
Order By: Relevance
“…In our study, only plants positive for introduced gene(s) were marked and subjected to further studies. Real-time quantitative PCR has emerged as a standard molecular technique to analyze relative expression of targeted genes (Maqbool et al, 2010;Rao et al, 2011;Anayol et al, 2016). In the present study, GUS and PCR positive transformants of Basma and Nail were subjected to qPCR and we observed that transgenic plants had increased expression of cry1Ac.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In our study, only plants positive for introduced gene(s) were marked and subjected to further studies. Real-time quantitative PCR has emerged as a standard molecular technique to analyze relative expression of targeted genes (Maqbool et al, 2010;Rao et al, 2011;Anayol et al, 2016). In the present study, GUS and PCR positive transformants of Basma and Nail were subjected to qPCR and we observed that transgenic plants had increased expression of cry1Ac.…”
Section: Discussionmentioning
confidence: 66%
“…The expression level of cry1Ac protein varied among different transgenic plants of both cultivars ( Figure 6). The variability in cry1Ac expression in transgenic crops has previously been reported (Olsen at al., 2005;Puspito et al, 2015;Anayol et al, 2016) and has been attributed to the regulatory nature of 35S promoter (Sunilkumar et al, 2012). The cry toxin amount varied among transgenic plants in T0 and T1 generations (Figures 6 and 10).…”
Section: Discussionmentioning
confidence: 99%
“…35S CaMV is widely used promoter in commercialized transgenic crops as well as for other research purposes. Being constitutive in nature, 35S promoter induces expression of foreign gene all tissues types during plant growth and development (Mi et al 2015;Anayol et al 2016). In the present study, cry1Ac expression was also studied under the control of wound specific AoPRI promoter.…”
Section: Discussionmentioning
confidence: 82%
“…The construction of plant expression cassette has been described in Anayol et al (2016) in detail and represented as Fig. 1.…”
Section: Description Of Expression Constructsmentioning
confidence: 99%
“…The use of tissue specific or light inducible promoter is being considered a more promising strategy in order to address public concerns on biosafety of transgenic crops (Anayol et al, 2016). The use of light inducible promoter restricted cry1Ab expression to aerial parts of transgenic potatoes and resulted in enhanced resistance against PTM.…”
Section: Insect Resistant Potatoesmentioning
confidence: 99%